Method for synergistically preparing high-purity hydrogen fluoride from fluorine-containing material
Through the method of acid and alkali wet treatment and modified microporous ceramic separation and purification, the problem of complex and high cost treatment of fluorine-containing waste from aluminum electrolysis in the existing technology has been solved, and the preparation of high-purity hydrogen fluoride and the effective utilization of resources have been achieved. .
Patent Information
- Application Number
- CN202411654681.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the treatment method of aluminum electrolytic fluorine-containing waste is complex, has high cost, and the prepared hydrogen fluoride impurity content is high, so it cannot be put directly into the production line.
Through acid and alkali wet treatment of overhaul slag and carbon residue, fluorine and aluminum are extracted, regenerated cryolite is prepared, and blended with aluminum electrolyte, and concentrated sulfuric acid is added for reaction to generate hydrogen fluoride gas, which is separated and purified through modified microporous ceramics. High-purity hydrogen fluoride is obtained.
The coordinated use of large residue, carbon residue, and aluminum electrolytes, simplified the process process, reduced costs, increased the extraction and purity of hydrogen fluoride, and could be directly used for production lines.
Smart Images

Figure BDA0005141849230000101 
Figure BDA0005141849230000111 
Figure BDA0005141849230000112
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fluorine-containing waste material recovery and treatment, and in particular, relates to a method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials. Background Art
[0002] The overhaul slag in aluminum electrolysis is a solid waste that is inevitably produced in the production process of electrolytic aluminum. It mainly comes from the waste cathode materials replaced during the overhaul of the electrolytic cell. Among them, the waste cathode carbon block specifically refers to the graphite cathode that has been corroded by the electrolyte. The main component is carbon with a graphitization degree of 85%, accounting for about 65%. In addition, it also contains fluorides in the form of cryolite, sodium fluoride, calcium fluoride, etc., accounting for about 30%. Because the overhaul slag contains a large amount of soluble fluorides and cyanides and other harmful substances, if it is not handled properly, it will cause serious pollution and harm to the environment, and cyanide is a highly toxic substance, which is extremely harmful to the human body and the environment.
[0003] Therefore, in the prior art, aluminum electrolysis waste is usually processed again and recycled, such as a method for utilizing aluminum electrolysis fluorine-containing waste and surplus electrolyte resources disclosed in patent CN111892022A, which crushes and grinds aluminum electrolysis fluorine-containing waste and surplus electrolyte into electrolyte powder, adds electrolyte powder and acid into a negative pressure reactor for reaction, and obtains hydrofluoric acid product after condensation and rectification of hydrogen fluoride generated by the reaction. However, since the reaction of this method is carried out under a negative pressure system, the production process is complicated, the equipment requirements are high, and the cost is high, and the hydrofluoric acid prepared by it has a high impurity content and insufficient concentration, so it cannot be directly put into production line for use.
[0004] Therefore, based on the above description, there is an urgent need for a method for the synergistic preparation of high-purity hydrogen fluoride using fluorine-containing materials, which can utilize overhaul slag, carbon slag, and aluminum electrolyte to synergistically prepare high-purity hydrogen fluoride gas for direct use. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for the synergistic preparation of high-purity hydrogen fluoride by fluorine-containing materials, which can utilize overhaul slag, carbon slag, and aluminum electrolyte together to synergistically prepare hydrogen fluoride gas, and further purify it, and finally dissolve it to obtain high-concentration hydrofluoric acid so that it can be directly put into use in the production line, thereby realizing resource recycling and avoiding fluoride pollution to the environment.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials comprises the following steps:
[0008] S1. Mixing aluminum electrolysis overhaul slag and carbon slag, crushing and ball milling to obtain mixed powder;
[0009] S2, slurrying the mixed powder, and then sequentially performing pressurized alkali leaching and oxidation to remove cyanide, and then filtering and separating to obtain an alkali leaching solution and an alkali leaching residue; then acid leaching the alkali leaching residue to obtain an acid leaching solution; mixing the alkali leaching solution and the acid leaching solution, and precipitating after continuous stirring and reaction, and separating to obtain regenerated cryolite;
[0010] S3, the regenerated cryolite is pulverized and mixed with aluminum electrolyte, and then concentrated sulfuric acid is added, followed by stirring and heating to obtain a mixed gas;
[0011] S4. Separating and purifying the mixed gas by using modified microporous ceramics to obtain hydrogen fluoride gas.
[0012] In the present invention, the fluorine and aluminum in the aluminum electrolysis overhaul slag and carbon slag (the mass ratio of the aluminum electrolysis overhaul slag to the carbon slag is 2:1-5:1) are leached out by acid and alkali wet treatment, and the acid leaching solution and the alkali leaching solution are further mixed in proportion, and the regenerated cryolite (Na3Al1 F6); further blending the regenerated cryolite with the aluminum electrolyte in a mass ratio of 1:9-5:5, and then further drying, crushing, and grinding to obtain a powder of 80-200 mesh, further adding 1.2-1.5 times the concentration of 98% concentrated sulfuric acid to mix, reacting under stirring and heating conditions to obtain reaction slag and hydrogen fluoride gas, and again separating and purifying the hydrogen fluoride gas through the modified microporous ceramic to obtain high-purity hydrogen fluoride gas, so that the modified microporous ceramic is further rinsed repeatedly with a small amount of deionized water to obtain high-concentration hydrofluoric acid, which is directly put into the production of aluminum electrolysis flux (aluminum fluoride, etc.), and the modified microporous ceramic can also be cleaned in time for reuse; during the reaction of the regenerated cryolite and aluminum electrolyte blended powder with sulfuric acid to prepare hydrogen fluoride gas, the main reaction equation is as follows:
[0013] 2Na3AlF6+6H2SO4=3Na2SO4+Al2(SO4)3+12HF
[0014] 3Na3AlF6+2H2SO4=2Na2SO4+Na5Al3F 14 +4HF
[0015] 2Na3AlF6+3H2SO4=3Na2SO4+2AlF3+6HF
[0016] 2Na5Al3F 14 +5H2SO4=5Na2SO4+6AlF3+10HF
[0017] 2Na5Al3F 14 +14H2SO4=5Na2SO4+3Al2(SO4)3+28HF
[0018] 2AlF3+3H2SO4=Al2(SO4)3+6HF
[0019] 2NaF+H2SO4=Na2SO4+2HF
[0020] In the present invention, the modified microporous ceramics contain the following raw materials in percentage by mass: 10-15% calcium oxide powder, 3-8% polyvinyl alcohol, 8-10% ammonium fluoride powder, 50-60% diatomaceous earth and 15-20% fly ash.
[0021] In the present invention, the preparation method of the modified microporous ceramic comprises the following steps:
[0022] s1. At room temperature, the calcium oxide powder, the polyvinyl alcohol and the ammonium fluoride powder are mixed, and then the diatomaceous earth and the fly ash are added and mixed to obtain a mixed raw material;
[0023] s2, subjecting the mixed raw materials to compression molding and drying in sequence to obtain a microporous ceramic blank;
[0024] s3: Under the protection of an inert gas, the microporous ceramic blank is sintered at a high temperature to obtain a modified microporous ceramic.
[0025] In the present invention, the characteristic of ammonium fluoride being easy to absorb moisture is utilized, and polyvinyl alcohol is further adopted. A large amount of hydroxyl groups in the polyvinyl alcohol are utilized, and hydrogen bonds are formed between the hydroxyl groups and the water in the ammonium fluoride after absorbing moisture, thereby playing a drying role, and preventing the ammonium fluoride from being decomposed due to long-term moisture absorption. In addition, polyvinyl alcohol is pre-blended with calcium oxide and ammonium fluoride to initially form agglomerates with a small volume, and then diatomaceous earth and fly ash are added for blending, and the mixture is molded to form a spherical blank. After gradient temperature rise sintering, the ammonium fluoride reacts with calcium oxide to generate calcium fluoride and ammonia. Meanwhile, the agglomerates in the spherical blank disappear after sintering, and pores with a large pore wall surface area are formed. In addition, polyvinyl alcohol can improve the flow of the sintering system and the film-forming property after losing the solvent at high temperature, and can generate a bubbling phenomenon in the sintering system during the escape process of ammonia, thereby forming a stable three-dimensional mesh pore structure, so that hydrogen fluoride in the mixed gas is retained under the action of calcium fluoride on the pore wall surface, thereby realizing the separation and enrichment of hydrogen fluoride.
[0026] The beneficial effects of the present invention are:
[0027] The present invention uses acid and alkali wet treatment to fully extract fluorine and aluminum in aluminum electrolysis overhaul slag and carbon slag, and obtains regenerated cryolite by mixing acid leaching solution and alkali leaching solution in proportion and neutralizing them; the regenerated cryolite is mixed with aluminum electrolyte, concentrated sulfuric acid is added and mixed, and reacted under stirring and heating conditions to obtain reaction slag and hydrogen fluoride gas. Compared with hydrogen fluoride obtained by extracting using a negative pressure system in the prior art, the extraction method of the present invention is simpler and the extraction amount of hydrogen fluoride is high;
[0028] The hydrogen fluoride gas is separated and purified again through the modified microporous ceramic to obtain high-purity hydrogen fluoride gas, so that the modified microporous ceramic can be repeatedly rinsed with a small amount of deionized water to obtain high-concentration hydrofluoric acid, which is directly used in the production of aluminum electrolysis flux (aluminum fluoride, etc.), fully realizing the resource utilization of aluminum electrolysis waste, without the need to use negative pressure equipment, reducing the complicated process flow of hydrogen fluoride chemical washing liquid reaction and impurity removal, reducing production costs, and improving production efficiency. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] Example 1
[0031] This embodiment provides a method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials, comprising the following steps:
[0032] (1) Raw material preparation
[0033] Aluminum electrolysis overhaul slag: 100kg
[0034] Carbon slag: 50kg
[0035] Preparation of modified microporous ceramics:
[0036] Raw materials: calcium oxide powder 12%, polyvinyl alcohol 5%, ammonium fluoride powder 8%, diatomaceous earth 55%, fly ash 20%.
[0037] Calcium oxide powder, polyvinyl alcohol and ammonium fluoride powder were blended at a stirring speed of 175 r / min for 45 minutes. Diatomaceous earth and fly ash were added, the stirring speed was increased to 250 r / min, and the stirring was continued for 25 minutes. The mixed raw materials were molded into a sphere and dried to obtain a spherical microporous ceramic blank. Under nitrogen protection, the temperature was raised to 980°C and sintered for 4 hours to obtain a spherical modified microporous ceramic.
[0038] (2) Mixing and slurry preparation
[0039] The aluminum electrolysis overhaul slag and carbon slag are mixed, crushed by a crusher to a particle size of less than 5 mm, and then ball-milled by a ball mill to an average particle size of 0.55 mm to obtain a mixed powder.
[0040] (3) Pressure alkaline leaching and oxidation decyanation
[0041] Add the mixed powder into the reactor, add NaOH solution at a concentration of 65g / L, with a liquid-to-solid ratio of 10:1, and mix the slurry evenly. Perform pressurized alkali leaching at 110°C and a pressure of 0.25Mpa for 1.5 hours. Use ozone as an oxidant to perform oxidative decyanation treatment for 2.5 hours. After filtration and separation, obtain alkali leaching solution and alkali leaching residue.
[0042] (4) Acid leaching and preparation of regenerated cryolite
[0043] The alkali leaching residue was added to another reactor, and the solid content of the slurry was adjusted to 17.5% with concentrated sulfuric acid, and the acid leaching was continued for 6 hours at 65°C. The alkali leaching solution and the acid leaching solution were mixed in a mass ratio of 3:1, stirred at 90°C at a speed of 700r / min for 3 hours, and then precipitated and separated to obtain the regenerated cryolite.
[0044] (5) Gas generation
[0045] The regenerated cryolite is pulverized and mixed with aluminum electrolyte in a mass ratio of 1:9. After drying, crushing and grinding, 80-mesh powder is obtained. 1.2 times the volume of 98% concentrated sulfuric acid is added to the powder, and the stirring speed is maintained at 600r / min. Subsequently, oil bath heating is used to raise the oil temperature to 290°C and keep it warm for 4 hours to generate a mixed gas.
[0046] (6) Gas separation and purification
[0047] Spherical modified microporous ceramics were used as fillers in the separation tank to separate and purify the dried mixed gas. The feed flow rate was 20 ml / s, and hydrogen fluoride gas was obtained after separation for 30 minutes.
[0048] Example 2
[0049] (1) Raw material preparation
[0050] Aluminum electrolysis overhaul slag: 150kg
[0051] Carbon slag: 75kg
[0052] Preparation of modified microporous ceramics:
[0053] Raw materials: calcium oxide powder 15%, polyvinyl alcohol 9%, ammonium fluoride powder 11%, diatomaceous earth 50%, fly ash 15%.
[0054] The raw materials were blended, and the stirring speeds were 150 r / min (front) and 300 r / min (back), and the stirring time was 60 minutes and 20 minutes, respectively.
[0055] After compression molding and drying, the microporous ceramic blank is placed in an argon environment and heated to 1000° C. for sintering for 5 hours to obtain a spherical modified microporous ceramic filler.
[0056] (2) Mixing and slurry preparation
[0057] After the raw materials are mixed, they are crushed by a crusher to a particle size of less than 3 mm, and then ball-milled by a ball mill to an average particle size of 0.45 mm.
[0058] (3) Pressure alkaline leaching and oxidation decyanation
[0059] The mixed powder was added to the reactor, and NaOH solution was added at a concentration of 70 g / L, with a liquid-to-solid ratio of 12:1. The pressurized alkali leaching was carried out at 120°C and a pressure of 0.3 MPa for 2 hours. Calcium hypochlorite was used as an oxidant, and the treatment time was 3 hours.
[0060] (4) Acid leaching and preparation of regenerated cryolite
[0061] During acid leaching, the solid content of the slurry was adjusted to 20%, and the acid leaching was continued for 7 hours at 70° C. The alkaline leaching solution and the acid leaching solution were mixed at a mass ratio of 2.5:1 and stirred at 85° C. at a speed of 800 r / min for 4 hours.
[0062] (5) Gas generation
[0063] The regenerated cryolite is pulverized and mixed with aluminum electrolyte in a mass ratio of 2:7. After drying, crushing and grinding, a 150-mesh powder is obtained. 1.3 times the volume of 98% concentrated sulfuric acid is added to the powder, and the stirring speed is maintained at 650 r / min. Subsequently, oil bath heating is used to raise the oil temperature to 300°C and keep it warm for 4 hours to generate a mixed gas.
[0064] (6) Gas separation and purification
[0065] Spherical modified microporous ceramics were used as separation tank fillers to separate and purify the dried material. The feed flow rate was 30 ml / s and the separation time was 25 min.
[0066] Example 3
[0067] (1) Raw material preparation
[0068] Aluminum electrolysis overhaul slag: 250kg
[0069] Carbon slag: 50kg
[0070] Preparation of modified microporous ceramics:
[0071] Raw materials: calcium oxide powder 10%, polyvinyl alcohol 2%, ammonium fluoride powder 8%, diatomaceous earth 60%, fly ash 20%.
[0072] Calcium oxide powder, polyvinyl alcohol and ammonium fluoride powder were blended at a stirring speed of 200 r / min for 30 minutes. Diatomaceous earth and fly ash were added, and the stirring speed was increased to 250 r / min for 25 minutes. The mixed raw materials were molded into a sphere and dried to obtain a spherical microporous ceramic blank. The microporous ceramic blank was placed in a nitrogen environment and heated to 1100°C for sintering for 3 hours.
[0073] (2) Mixing and slurry preparation
[0074] After the raw materials are mixed, they are crushed to a particle size of less than 2 mm using a crusher, and then ball-milled to an average particle size of 0.40 mm using a ball mill.
[0075] (3) Pressure alkaline leaching and oxidation decyanation
[0076] The mixed powder was added to the reactor, and NaOH solution was added at a concentration of 60 g / L, with a liquid-to-solid ratio of 8:1. The pressurized alkaline leaching was carried out at 100°C and a pressure of 0.2 MPa for 1 hour. A mixture of ozone and calcium hypochlorite was used as an oxidant, and the treatment time was 2 hours.
[0077] (4) Acid leaching and preparation of regenerated cryolite
[0078] During acid leaching, the solid content of the slurry was adjusted to 15%, and the acid leaching was continued for 5 hours at 50° C. The alkaline leaching solution and the acid leaching solution were mixed at a mass ratio of 3.5:1 and stirred at 90° C. at a speed of 600 r / min for 3.5 hours.
[0079] (5) Gas generation
[0080] The regenerated cryolite is pulverized and mixed with aluminum electrolyte in a mass ratio of 4:5. After drying, crushing and grinding, a 180-mesh powder is obtained. 1.5 times the volume of 98% concentrated sulfuric acid is added to the powder, and the stirring speed is maintained at 650r / min. Subsequently, oil bath heating is used to raise the oil temperature to 300°C and keep it warm for 4.5 hours to generate a mixed gas.
[0081] (6) Gas separation and purification
[0082] Spherical modified microporous ceramics were used as fillers in the separation tank to separate and purify the dried mixed gas. The feed flow rate was 10 ml / s and the processing time was 40 min.
[0083] Comparative Example 1
[0084] The difference between this comparative example and Example 1 is that conventional acid leaching is adopted, and the pressure alkali leaching and oxidation cyanide removal steps are not performed.
[0085] Comparative Example 2
[0086] The difference between this comparative example and Example 1 is that a ceramic membrane filter tube is used as the filter medium (ceramic membrane filter tube model GC-GLG-01 of Jiangxi Guoci Environmental Protection Technology Co., Ltd.).
[0087] Test Example 1
[0088] The mixed gas prepared in Example 1-3 and Comparative Example 1-2 was extracted, and the main components and contents (by volume percentage) of the mixed gas before filtration were detected by gas chromatography;
[0089]
[0090]
[0091] Test Example 2
[0092] The hydrogen fluoride gas after filtration in Example 1-3 and Comparative Example 1-2 was extracted, and the purity of hydrogen fluoride was tested by a gas detector. The test results are shown in Table 2 below:
[0093] Table 2
[0094]
[0095] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials, characterized in that: The following steps are involved: S1. Mixing aluminum electrolysis overhaul slag and carbon slag, crushing and ball milling to obtain mixed powder; S2, slurrying the mixed powder, and then sequentially performing pressurized alkali leaching and oxidation to remove cyanide, and then filtering and separating to obtain an alkali leaching solution and an alkali leaching residue; then acid leaching the alkali leaching residue to obtain an acid leaching solution; mixing the alkali leaching solution and the acid leaching solution, and precipitating after continuous stirring and reaction, and separating to obtain regenerated cryolite; S3, the regenerated cryolite is pulverized and mixed with aluminum electrolyte, and then concentrated sulfuric acid is added, followed by stirring and heating to obtain a mixed gas; S4. Separating and purifying the mixed gas by using modified microporous ceramics to obtain hydrogen fluoride gas.
2. The method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials according to claim 1, characterized in that: In step S2, a NaOH solution with a concentration of 60-70 g / L is added to slurry the mixed powder to a liquid-to-solid ratio of 8:1-12:
1.
3. The method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials according to claim 2, characterized in that: In step S2, the treatment temperature of the pressurized alkali leaching is 100-120°C, the concentration of NaOH is 50-100g / L, the pressure is 0.2-0.3Mpa, and the reaction time is 1-2h.
4. The method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials according to claim 1, characterized in that: In step S2, the oxidative decyanation uses at least one of ozone and calcium hypochlorite as an oxidant, and the oxidation treatment is carried out for 2-3 hours.
5. The method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials according to claim 1, characterized in that: In step S2, the alkali leaching residue is adjusted to have a solid content of 15-20% by using concentrated sulfuric acid, and then continuously acid leaching is performed at a temperature of 50-70° C. for 5-7 hours.
6. The method for preparing high-purity hydrogen fluoride by synergistic use of fluorine-containing materials according to claim 1, characterized in that: In step S2, the mass ratio of the alkaline leaching solution to the acid leaching solution is 3.5:1-2.5:1; the stirring speed is 600-800 r / min, the temperature is 85-90° C.; and the stirring time is 3.5-4 h.
7. The method for preparing high-purity hydrogen fluoride by using fluorine-containing materials according to claim 1, characterized in that: In step S4, when the modified microporous ceramic is used to separate and purify the mixed gas, the feed flow rate is 10-30 ml / s and the separation time is 20-40 min.
8. The method for preparing high-purity hydrogen fluoride by using fluorine-containing materials according to any one of claims 1 to 7, characterized in that: The modified microporous ceramic comprises the following raw materials in percentage by mass: 10-15% of calcium oxide powder, 3-8% of polyvinyl alcohol, 8-10% of ammonium fluoride powder, 50-60% of diatomaceous earth and 15-20% of fly ash.
9. The method for preparing high-purity hydrogen fluoride by using fluorine-containing materials according to claim 8, characterized in that: The preparation method of the modified microporous ceramic comprises the following steps: s1. At room temperature, the calcium oxide powder, the polyvinyl alcohol and the ammonium fluoride powder are mixed, and then the diatomaceous earth and the fly ash are added and mixed to obtain a mixed raw material; s2, subjecting the mixed raw materials to compression molding and drying in sequence to obtain a microporous ceramic blank; s3: Under the protection of an inert gas, the microporous ceramic blank is sintered at a high temperature to obtain a modified microporous ceramic.
10. The method for preparing high-purity hydrogen fluoride by using fluorine-containing materials according to claim 9, characterized in that: In step s1, when the calcium oxide powder, the polyvinyl alcohol and the ammonium fluoride powder are blended, the stirring speed is 150-200 r / min and the stirring time is 30-60 min; when the diatomaceous earth and the fly ash are added for blending, the stirring speed is 200-300 r / min and the stirring time is 20-30 min.